Pengaruh Materialitas, Etika Auditor dan Independensi Auditor Terhadap Opini Audit - Ilhamsyah, Haikal Rafif; Nopiyanti, Anita; Mashuri, Ayunita Ajengtiyas Saputri (Institut Bisnis dan Informatika Kesatuan, 2020)
Thisxresearchzisxusingxquantitivezstudyzaimedxtossee whatever theresare the effect ofsmateriality, auditor ethics and auditor independence on thesprovision of giving auditsopinion. This study uses primary data with respondents are senior auditors working in accountant publik firm in the DKI Jakarta. Testing the hypothesis in the study was used Multiple Linier Regression Analysys using SPSS analisys tool with a significant level of 5% (0,05). The Result of these test indicate that (1) there is significant influence materiality on provision of audit opinion, (2) there is no significant influence auditor ethics on provision of audit opinion, (3) there is no significant influence auditor independence on provision of audit opinion